2016
DOI: 10.1002/2016gl069117
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying manganese and nitrogen cycle coupling in manganese‐rich, organic carbon‐starved marine sediments: Examples from the Clarion‐Clipperton fracture zone

Abstract: Extensive deep‐sea sedimentary areas are characterized by low organic carbon contents and thus harbor suboxic sedimentary environments where secondary (autotrophic) redox cycling becomes important for microbial metabolic processes. Simulation results for three stations in the Eastern Equatorial Pacific with low organic carbon content (<0.5 dry wt %) and low sedimentation rates (10−1–100 mm ky−1) show that ammonium generated during organic matter degradation may act as a reducing agent for manganese oxides belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 54 publications
3
55
0
Order By: Relevance
“…In these sediments, dissolved O 2 concentrations are high at the top and the bottom of the retrieved sediments and lower in-between. Such pore-water profiles can be explained by downward O 2 diffusion from oxygen-rich seawater as well as upward O 2 diffusion from oxygen-rich water migrating through the basaltic basement Mogollón et al, 2016;Ziebis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In these sediments, dissolved O 2 concentrations are high at the top and the bottom of the retrieved sediments and lower in-between. Such pore-water profiles can be explained by downward O 2 diffusion from oxygen-rich seawater as well as upward O 2 diffusion from oxygen-rich water migrating through the basaltic basement Mogollón et al, 2016;Ziebis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Low Mn 2+ together with the rapid decrease in nitrate at 0-2 cm depth at D3 (Fig. 2f, g) also suggested that dissolved reduced manganese might act as a reducing agent for nitrate, as was suggested by Aller et al (1998) in the Panama Basin and Mogollón et al (2016) in the deep-sea sediment of the ClarionClipperton fracture zone in the northeast equatorial Pacific.…”
Section: Partitioning Of C Org Oxidation In Accordance With the Distrmentioning
confidence: 85%
“…Adopting the sediment accumulation rate of 0.07 cm year −1 in the UB determined at a station 50 km from D3 (Cha et al, 2005), the average Mn (DCA) content of 1.1 µmol cm −3 at 10-20 cm depth (Fig. 2g) corresponds to a flux for permanent burial of 0.002 mmol m −2 d −1 or just 0.03 % of the Mn reduction rate (Table 3) -i.e., an Mn atom is recycled 3800 times before it finally gets buried, first by stripping from the particles that settle to the seafloor and subsequently, over and over, by reductive dissolution of the Mn oxides that from by reoxidation in the oxic surface layer (or, potentially, in the nitrate zone; Aller et al, 1998;Mogollón et al, 2016). This is a much more extensive recycling than found in the Mn sediment of Skagerrak (130-260 times; Canfield et al, 1993b).…”
Section: Source Of High Mn Oxide Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The geochemical variability which was discovered in the undisturbed as well as disturbed sites elucidates that the deepsea is a highly complex system that is still poorly understood as has also been recently shown for the CCZ (Mewes et al, 2014Mogollón et al, 2016;Kuhn et al, 2017;Volz et al, in review). With respect to polymetallic nodule mining, it will be necessary to carry out baseline studies on the geochemistry of the potentially impacted sites and reference sites for quite a high number of locations to assess the heterogeneity of both, the natural area and the types of impact.…”
Section: Resultsmentioning
confidence: 99%